rDNA-FISH pattern in selected Hieracium species representing different ploidy levels - Aleksandra Grabowska-Joachimiak; Dagmara Kwolek; Elżbieta Pięta; Zbigniew Szeląg; Andrzej J. Joachimiak (Acta Societatis Botanicorum Poloniae, 2023)
Polyploid species of Hieracium s.str. are near-obligatory apomicts capable of producing non-reduced pollen grains and intrageneric crossing with sexual diploid species. Most probably, such a mating system leads to the emergence of separate lineages of apomictic plants with increased ploidy levels, each of which has a complete set of genomes of its putative (most probably triploid) apomictic parent. The correct identification of such lineages could facilitate taxonomic and phylogenetic research in Hieracium . In this paper, we analyzed the distribution of the 5S and 45S rDNA segments in the karyotypes of six selected Hieracium taxa, representing all ploidy levels reported in the genus: H. alpinum 2x, H. alpinum 3x, H. schustleri 4x, H. chrysostyloides 5x ( H . sect. Alpina ) and H. bifidum 3x, H. levicaule 3x ( H . sect. Bifida ). The analyzed rDNA markers suggest that two taxa of the higher ploidy level (4x and 5x) belonging to H . sect. Alpina inherited three genomes from the triploid H. alpinum , which has 2:1 genomic composition with two genomes from diploid H. alpinum and one genome with an untypical 5S rDNA-bearing chromosome of unknown origin. H. bifidum and H. levicaule differ from each other in the rDNA distribution pattern, which suggests that H . sect. Bifida may be a less homogenous group of species.